Separation of CO2/CH4 through Carbon Tubular Membranes: Effect of Carbonization Temperature - Salleh, W.N.W.; Sazali, N.; Ismail, A.F. (Journal of Membrane and Separation Technology, 2014)
Carbon membranes have received much attention as advance materials in the gas separation technology due to their superior gas permeation performance and thermal and chemical stability. In order to increase the mechanical strength of the membrane, supported carbon membrane were produced using ceramic tube as support layer. Carbon tubular membranes were produced by carbonizing polymeric tubular membrane under different process parameter. In this study, carbon tubular membranes originating from Matrimid were prepared and characterized n term of its gas permeation properties. The preparation method involved dip-coating of the ceramic tubes with a Matrimid-based solution. The carbon tubular membranes were obtained by carbonization of the resultant polymeric tubular membrane under Argon gas flow in the horizontal tube furnace. The effects of the carbonization temperature on the gas permeation performance were investigated. Pure gas permeation tests were performed using CO2 and CH4 at room temperature with pressure 8 bars. The permeance and selectivity data indicate that the highest CO2/CH4 selectivity of 87.30 was obtained for carbon tubular membrane prepared at carbonization temperature of 850 ºC.